Search for unconventional superconductors among the YTE2Si2 compounds (TE = Cr, Co, Ni, Rh, Pd, Pt). (5th April 2017) - Pikul, A P; Samsel–Czekała, M; Chajewski, G; Romanova, T; Hackemer, A; Gorzelniak, R; Wiśniewski, P; Kaczorowski, D
Abstract: Motivated by the recent discovery of exotic superconductivity in YFe2 Ge2 we undertook reinvestigation of formation and physical properties of yttrium-based 1:2:2 silicides. Here we report on syntheses and crystal structures of the Y TE 2 Si2 compounds with TE   =  Cr, Co, Ni, Rh, Pd and Pt, and their low-temperature physical properties measurements, supplemented by results of fully relativistic full-potential local-orbital minimum basis band structure calculations. We confirm that most of the members of that family crystallize in a tetragonal ThCr2 Si2 -type structure (space group I 4/ mmm ) and have three-dimensional Fermi surface, while only one of them (YPt2 Si2 ) forms with a closely-related primitive CaBe2 Ge2 -type unit cell (space group P 4/ nmm ) and possess quasi-two-dimensional Fermi surface sheets. Physical measurements indicated that BCS-like superconductivity is observed only in YPt2 Si2 ( T c   =  1.54 K) and YPd2 Si2 ( T c   =  0.43 K), while no superconducting phase transition was found in other systems at least down to 0.35 K. Thermal analysis showed no polymorphism in both superconducting phases. No clear relation between the superconductivity and the crystal structure (and dimensionality of the Fermi surface) was observed.